Etiology and Perinatal Outcome of Polyhydramnios - Kollmann, M.; Voetsch, J.; Koidl, C.; Schest, E.; Haeusler, M.; Lang, U.; Klaritsch, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: To determine causes of polyhydramnios and the respective perinatal outcome.Materials and Methods: We retrospectively analyzed cases with polyhydramnios at the Medical University Graz, Austria from 2003 – 2011. Inclusion criteria were single deepest pocket ≥ 8 cm, amniotic fluid index ≥ 25 cm, each of the latter parameters > 95th percentile or subjective impression. Etiologies, including TORCH infection, diabetes and congenital malformations, as well as perinatal outcome were evaluated.Results: Out of 860 singleton pregnancies with polyhydramnios, 2.9 % had positive TORCH serology, 8.5 % had congenital anomalies, 19.8 % had maternal diabetes, and 68.8 % were idiopathic. The most common fetal anomalies were cardiac defects (32.9 %). Elective caesarean sections were more common in the groups with malformations and maternal diabetes. Low birth weight combined with severe polyhydramnios or maternal diabetes was associated with malformations.Conclusion: Diagnosis of polyhydramnios should prompt glucose-tolerance testing, detailed sonography including fetal echocardiography, and TORCH serology. Especially pregnancies with polyhydramnios and small fetuses as well as those with maternal diabetes should be carefully evaluated for malformations.
Keywords: obstetrics; fetus; ultrasound